A memória assombrada: um estudo da autorrepresentação no documentário animado Valsa com Bashir - Souza, Maria Ines Dieuzeide Santos (Universidade Federal de São Carlos, 2012)
This work aims to discuss processes of self-representation in animated documentaries, from the analysis of the film Waltz with Bashir (Ari Folman, 2008). With this analysis, it seeks to understand modes of articulation between the field of documentary and animation, using elements of both as a possibility of self-representation in films that are related to the shared historic world. For this purpose, it develops a reflection on the establishment of different perspectives in the field of documentary studies and the ways available for animation to create representations. In addition, it dialogues with the various historical and conceptual approaches about the animated documentary, developed significantly over the past fifteen years. Finally, it develops a critical analysis of what Bill Nichols (1994) calls performative documentary and the considerations of Michael Renov (2004) about documentaries that deal with the autobiographical, to understand the animation as a way to put the director in history and establish a continuity with the past, weaving relationships between elements of documentary and animated images that provide other senses to the reported.
Keywords: Documentário (Cinema); Animação (Cinematografia); Autobiografia; Valsa com Bashir; Animated documentary; Self-representation; Autobiographical documentary; Waltz with Bashir; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA